Formulation and optimization of a zinc oxide nanoparticle ink for printed electronics applications. (11th January 2018) - Suganthi, K S; Harish, K; Nair, Nitheesh M; Swaminathan, P
Abstract: In this work, we describe the preparation of a zinc oxide-ethylene glycol nanoparticle ink and the parameters that control the printing using a custom-built direct writer system. The ink (nanoparticle dispersion) was prepared using a two-step wet synthesis method, without using any surfactant. Its viscosity was found to be in the suitable range for printing and straight lines were printed on cleaned glass substrates. The influence of various printing parameters, such as total dispersed volume, number of printed layers, substrate temperature, drying temperature and time, and particle loading, on the morphology of the printed patterns was investigated. In-situ and post-printing drying of the printed pattern, at the same temperature, produced different morphologies, which can be attributed to the direction of heat transfer and solvent removal. Optimization of these printing parameters enabled us to obtain a continuous printed pattern with uniform morphology using a direct writing system, which can be extended to a variety of nanoparticle based inks.